Predictive factors of pathological lateral pelvic lymph node metastasis in patients without clinical lateral pelvic lymph node metastasis (clinical stage II/III): The analysis of data from the clinical trial (JCOG0212). Issue 3 (March 2019) - Komori, Koji; Fujita, Shin; Mizusawa, Junki; Kanemitsu, Yukihide; Ito, Masaaki; Shiomi, Akio; Ohue, Masayuki; Ota, Mitsuyoshi; Akazai, Yoshihiro; Shiozawa, Manabu; Yamaguchi, Takashi; Bandou, Hiroyuki; et al.
Abstract: Background: Mesorectal excision (ME) is the standard surgical procedure for lower rectal cancer. However, in Japan, total or tumor-specific ME with lateral pelvic lymph node dissection (LLND) is the standard surgical procedure for patients with clinical stages II or III lower rectal cancer, because lateral pelvic lymph node metastasis occasionally occurs in these patients. The aim of study was to elucidate the predictive factors of pathological lateral pelvic lymph node metastasis in patients without clinical lateral pelvic lymph node metastasis. Methods: Data form the clinical trial (JCOG0212) was analyzed. The JCOG0212 was a randomized controlled trial to confirm the non-inferiority of mesorectal excision alone to mesorectal excision with lateral lymph node dissection for clinical stage II/III patients who don't have clinical lateral pelvic lymph node metastasis in terms of relapse free survival. This study was conducted at a multitude of institution33 major hospitals in Japan. Among the 351 patients who underwent lateral lymph node dissection in the JCOG0212 study, 328 patients were included in this study. Associations between pathological lateral pelvic lymph node metastasis and preoperative and postoperative factors were investigated. The preoperative factors were age, sex, clinical stage, tumor location, distance from anal verge, tumor size, and short-axis diameter of lateral pelvic lymph node on computed tomography and the postoperative factors were pathological T, pathological N, and histological grade. Results: Among the 328 patients, 24 (7.3%) had pathological lateral pelvic lymph node metastasis. In multivariable analysis of the preoperative factors, patient age (p = 0.067), tumor location (p = 0.025), and short-axis diameter of lateral pelvic lymph node (p = 0.002) were significantly associated with pathological lateral pelvic lymph node metastasis. Conclusions: Patient age, tumor location, and short-axis diameter of lateral pelvic lymph node were predictive factors of pathological lateral pelvic lymph node metastasis.